Bevölkerungsentwicklung in Groß-Santiago zwischen 1970 und 1982.: Eine Analyse von Zensurergebnissen auf Distriktbasis - Bähr, Jürgen; Mertins, Günter (ERDKUNDE, 1985)
An attempt is made in the light of an analysis of population changes occurring in several sub-districts of Greater Santiago in the period between the two last population censuses of 1970 and 1982, based on small-area census units (distritos and comunas) to draw attention to the effects on the spatial growth of the city resulting from changed conditions in the political and juridicial sphere since the change of power in 1973. Two decisions by the new government in particular affect the development of the city: the liberalization of the residential and property market and the turning away from the previous practice of suffering illegal occupation of land. It was possible to prove that the results of this policy were frequently in contradiction with the goals being pursued. In spite of more properties being offered for sale, increasing property speculation led to the poorer population groups being increasingly less able to afford a plot of their own. Since there are no other possibilities of solving these housing problems, an adaptation of housing conditions to changes in the cycle of family life are largely prevented, and the ideal-typical migration cycle is disrupted. Instead of a spatial expansion of the city, there is a considerable population increase in already developed areas, so that the falling-off in the density gradient from central to peripheral areas has in part been reversed.